Akkermansia muciniphila attenuates LPS-induced acute kidney injury by inhibiting TLR4/NF-κB pathway. Issue 1 (11th November 2022) - Shi, Jun; Wang, Feng; Tang, Lei; Li, Zhiqiang; Yu, Manshu; Bai, Yu; Weng, Zebin; Sheng, Meixiao; He, Weiming; Chen, Yugen
Abstract: Acute kidney injury (AKI) is a global public health hazard with high morbidity and mortality. Sepsis accounts for nearly half of all causes of AKI. Scientists have made a great effort to explore effective therapeutic agents with limited side effects in the treatment of AKI, but have had little success. With the development of gut flora study, Akkermansia muciniphila ( A. muciniphila ) has been proven to prevent different organs by regulating the inflammatory response. However, the reno-protective function is still unknown. Here, the AKI model was induced using lipopolysaccharide (LPS) in mice with or without pretreatment of A. muciniphila . Renal function and histological change were measured. Inflammatory factors were detected by ELISA and rt-PCR. TLR4/NF-κB signaling factors and NLRP3 inflammasome were tested by western blot and immunohistochemistry. Pretreatment of A. muciniphila markedly inhibited inflammatory response and ameliorated kidney histopathological changes. Furthermore, the TLR4, p-NF-κB p65, and downstream IκBα were notably activated in the model group and inhibited by A. muciniphila . A similar effect was found in the regulation of NLRP3 inflammasome. In conclusion, pretreatment with A. muciniphila could protect against LPS-induced AKI by inhibition of the TLR4/NF-κB pathway and NLRP3 inflammasome activation. It may be a new therapeutic strategy for AKI prevention and treatment in the future. Abstract : Akkermansia muciniphila, a beneficial gut commensal, could protect against LPS-induced acute kidney injury by inhibition of the TLR4/NF-κB pathway and the NLRP3 inflammasome activation.